Strength training improves 5-min all-out performance following 185 min of cycling - Rønnestad, B. R.; Hansen, E. A.; Raastad, T. (Scandinavian Journal of Medicine & Science in Sports, 2011)
To investigate the effects of heavy strength training on the mean power output in a 5-min all-out trial following 185 min of submaximal cycling at 44% of maximal aerobic power output in well-trained cyclists. Twenty well-trained cyclists were assigned to either usual endurance training combined with heavy strength training [E+S; n=11 (male=11)] or to usual endurance training only [E; n=9 (male=7, female=2)]. The strength training performed by E+S consisted of four lower body exercises [3× 4-10 repetition maximum (RM)], which were performed twice a week for 12 weeks. E+S increased 1 RM in half-squat (P>/=0.001), while no change occurred in E. E+S led to greater reductions than E in oxygen consumption, heart rate, blood lactate concentration, and rate of perceived exertion (P<0.05) during the last hour of the prolonged cycling. Further, E+S increased the mean power output during the 5-min all-out trial (from 371 ± 9 to 400 ± 13 W, P<0.05), while no change occurred in E. In conclusion, adding strength training to usual endurance training improves leg strength and 5-min all-out performance following 185 min of cycling in well-trained cyclists.